Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
0.94
Step-by-step explanation:
Formula; P(AUB) = P(A) + P(B) - P(AB).
P(A) = 0.7
P(B) = 0.8
P(AB) = 0.56
= 0.7 + 0.8 - 0.56
= 0.94
Hence, P(A U B) = 0.94
[RevyBreeze]
Answer:
P(A ∪ B) = 0.94
Step-by-step explanation:
P(A) = 0.7
P(B) = 0.8
P (A ∩ B) = 0.56
P(A ∪ B) = P(A) + P(B) - (A ∩ B)
⇒ P(A ∪ B) = 0.7 + 0.8 - 0.56
⇒ P(A ∪ B) = 0.94
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.